EFEKTIFITAS PEMBERDAYAAN INFAQ DAN SHADAQAH DALAM MENGEMBANGKAN PENDIDIKAN ANAK YATIM (Program My HEART for Yatim di LAZ Al-Azhar) - Ajeng Kartika Galuh; Leviandra Thariq Al Qasthari (Islamic Economics and finance in Focus, 2023)
This study is to determine the effectiveness of the "My HEART for Yatim" program which is one of the programs at LAZ Al-Azhar in developing orphan education. The research method used is qualitative with a case study approach. Data collection techniques used include interviews, observation, and documentation. The results showed that the program was very effective in developing orphan education. This program provides financial and non-financial support to orphans, such as basic needs of orphans, character and creed building, and skills training. The program also engages the local community for regular programs in providing support and assisting in running the program. The empowerment of infaq and shadaqah succeeded in supporting orphans and believing the community in donating to the program. The My HEART for Yatim program also provides opportunities for orphans to grow and develop optimally." My HEART for Yatim" which prioritizes the empowerment of infaq and shadaqah makes the program effective in improving the quality of education for orphans. With this program, it provides opportunities for orphans to grow and develop optimally.